Identification of Junior High School Students' Conceptual Understanding of Heat and Its Transfer Using CRI (Certainty of Response Index) Diagnostic Essay Tests - Mahsunah, Himmatul Izzah; Manasikana, Oktaffi Arinna; Menicol, Daren; Erlangga, Sony Yunior (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
Heat and its transfer is one of the physics materials that is useful in everyday life. Therefore, understanding the concept of heat and its transfer is very important for students. Concept understanding is categorized into certain criteria, namely understanding the concept, not understanding the concept and misconceptions. The aim of this research is to identify SMP/MTs students' understanding of the concept of heat and its transfer. The research subjects used were 19 students of MTs Hidayatus Salam Gresik class VIII-B. The research instrument used was an essay diagnostic test assisted by CRI (Certainty of Response Index). The results of the combination of student answers and the selected CRI scale showed that 47.32% of students understood the concept, 40.34% did not understand the concept, and 12.34% had misconceptions. Students' lack of conceptual understanding is more influenced by not understanding the concept than by misconceptions which is indicated by the average percentage value. In this case, misconceptions are not the main problem in the learning difficulties experienced by students regarding heat and transfer material.